TINGKAT KESEGARAN JASMANI SISWA SMPN 1 BANGKO KABUPATEN ROKAN HILIR - ', M.Muhardi; ', Saripin; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, The background of the problem in this study originated from the observation while at SMPN 1 Bangko during studied hours penjasorkes lasted many students are less eager to do the activities and also many are tired. Due to the lack of accurate data on the physical fitness of students of SMPN 1 Bangko researcher conducted a study that aims to determine how the level of physical fitness SMPN 1 Bangko students. This type of research is descriptive quantitative research. This study describes clearly how the physical fitness level of students in SMPN 1 Bangko Rokan Hilir. This research data obtained from the TKJI test result. The sample in this study is the male students class VII and VIII of 20 people (purposive sampling). Based on the research results can be concluded as follows: overall physical fitness of students in SMP Negeri 1 Bangko Rokan Hilir can be categorized as less as per the norm TKJI which is located at 10-13, including the category of less value where that scored 10-13 with percentage highest students ie 80% or as much as 16 respondents.Keywords : Level, Physical Fitness